HUBUNGAN KELENGKAPAN PENGISIAN RESUME DENGAN KETEPATAN PEMBUATAN SURAT KETERANGAN MEDIS DI RS. BETHESDA - , AJENK VINDIANA ALFIO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background : Resume is a summary of the entire term care and treatment of patients . This sheet must be signed by the patient's treating physician. Incomplete medical resume sheet affects the medical records clerk job, especially the manufacture of Medical Certificate. Based on preliminary studies in hospital . Bethesda Yogyakarta shows there are quite a lot of sheet resume incomplete . And based on the results of interviews incompleteness resume charging impact on the manufacture of Medical Certificate . Objective: To determine the percentage of completeness resume medical inpatients and precision manufacturing of Medical Certificate in Bethesda Hospital completeness and determine the relationship of filling completeness resume with precision of medical sertificate in Bethesda Hospital. Methods: The design of this study used a descriptive research methods with quantitative approaches and cross-sectional study design . The population in this study is a medical resume sheet that will be used for the manufacture of a medical certificate with a sample of 112 resumes . Statistical analysis of the data using the Spearman Rank test . Results: The percentage of occupancy medical resume is the identity of the item charged at 99 % , the diagnosis was 74 % filled , action items by 37 % , 71 % history summaries , lab results by 62 % , therapy/treatment by 61 % , amounting to a state home 55 % , recommended by 32 % , on 54% of doctors by 67 % , and the signatures of 75% . Medical Certificate of Appropriateness manufacture accuracy percentage of 75% and the percentage occupancy of 25% . Based on the statistical test is a significant correlation between the completeness of medical resume charging sheet with precision manufacture of Medical Certificate with p value = 0.053